âThe âEnglish Schoolâ, South East Asia, and Indonesia: Locating and Defending Productive âmiddle groundâ - Quayle, Linda (Jurnal Hubungan Internasional, 2013)
This article elaborates that a pluralist English School perspective offers a number of possibilities that are useful in analysing SEA. Its prime contribution is to help locate the middle ground that is often missing from theoretical debates. Thus, it can bridge parallel discourses, whether they be realist and constructivist, or realist and liberal. It can also provide a socially oriented understanding of the role of great powers â an understanding that provides a much more subtle interpretation of what Indonesia offers the region, and the challenges it faces there.